Critérios sustentáveis nas licitações de serviços da Superintendência de Orçamento e Finanças da Universidade Federal da Paraíba - Almeida Neto, Severino Cidalino de (2021)
Over the years, the environment has abruptly supported strong deterioration and excessive exhaustion of its natural resources and, if there is no strong reduction in irresponsible, unrestrained and unsustainable consumption, there will be a clear compromise in access to a balanced and natural environment. healthy for future generations, which, over time, puts the very livelihood of the human species at risk. Thus, it is known that the balance between the correct consumption of natural resources and awareness of the sustainable demand for products is a tripartite responsibility between the State, the market and society. In this sense, this work aims to analyze the practice of the Superintendence of Budget and Finance (SOF) of the Federal University of Paraíba (UFPB) regarding the adoption of sustainable criteria included in notices in the bidding for services in the sector, in the period from 2015 to 2019. This research goes through the history of sustainability in Brazil and in the world, addresses its concept, exposes its dimensions and enters into sustainable public management, focusing on the Environmental Agenda of Public Administration (A3P). Furthermore, it addresses sustainability within the scope of Higher Education Institutions (HEIs), presents the theme about sustainable universities and finally analyzes the sustainable public procurement of the Bidding and Contracts Commission of the Superintendence of Budget and Finance of the Federal University of Paraíba (CLC/SOF/UFPB). As for the methodology, the assessment of the documents was carried out based on the qualiquantitative analysis of the notices of the selected bids from the adoption of its own evaluation method, with an exploratory and descriptive bias, given the nature of applied research and case study, in addition to being a documentary and bibliographic work, while also bringing to light a detailed survey that uses institutional documents and public data contained in the Federal Government Procurement Portal to enable the assessment of the objectives proposed here. As a final product contribution, this research prepares a practical manual for improving the use of sustainability criteria in public procurement of services carried out by the management of CLC/SOF/UFPB, in order to provide green and objective solutions throughout the purchasing process, from its initial phase (contracting planning phase) to the phase in which the State chooses a more advantageous proposal for itself. In this context, this research seeks to improve the promotion of sustainable development in the bidding processes of the aforementioned institutional sector.